Creating and Implementing a Website Using the Representation Learning Cycle (RLC) Model: An Effort to Enhance Understanding of Chemical Concepts and Representations in Chemical Equilibrium - Herunata, Herunata; Puteri, Evelyn (J-PEK (Jurnal Pembelajaran Kimia), 2024)
This study investigates the challenges students encounter when trying to comprehend abstract concepts in chemistry, with a primary focus on chemical equilibrium. The research aims to develop and implement website-based teaching materials grounded in the Representation Learning Cycle (RLC) model to enhance students' comprehension of chemical concepts and representations. Employing the ADDIE development model—consisting of analysis, design, development, implementation, and evaluation—the study utilises a quasi-experimental method with a nonequivalent control-group design. The effectiveness of the teaching materials is assessed through pretest and posttest measures of students' understanding. Results indicate that the developed website-based materials are feasible, achieving a validator test score of 92.5% and a readability score of 96.3%, both categorised as very feasible. The N-Gain Score of 0.69 suggests a sufficient level of effectiveness, while the Mann-Whitney Test yielded a result of 0.02, below the significance threshold of 0.05. Consequently, it can be concluded that the developed teaching materials significantly enhance students' understanding of chemical concepts and representations.